Analysis of Rock Magnetic Susceptibility in a Local Fault Zone at Sangkrek, Kulon Progo Regency - Muaffi, Nadzif; Fikri Niyartama, Thaqibul; Budi Wibowo, Nugoho; Rosyida, Hana (Sunan Kalijaga Journal of Physics, 2025)
This study aims to analyze the pattern of magnetic anomaly distribution and determine the rock magnetic susceptibility values as a basis for identifying a local fault zone in the Dusun Sangkrek area, Kokap District, Kulon Progo Regency. The geomagnetic method was employed, with data acquisition conducted at 60 observation points using a Proton Precession Magnetometer (PPM) G-856 at 100-meter intervals. The total magnetic field data were corrected for daily variations and the International Geomagnetic Reference Field (IGRF) to obtain the total magnetic anomaly (ΔT). The magnetic anomaly values range from –3,1 × 10² nT to 6,8 × 10² nT, where high anomalies are dominant in the northern part, composed mainly of andesitic rocks, while low anomalies are found in the western and southern parts, corresponding to the Sentolo and Alluvium Formations. Data processing stages include reduction to the pole (RTP), upward continuation, and two-dimensional (2D) modeling to characterize subsurface magnetic variations. The modeling results indicate that the magnetic susceptibility of rocks varies between 1,0 × 10⁻⁴ and 1,1 × 10⁻¹ SI, with higher values associated with andesite and brecciated andesite, and lower values corresponding to siltstone, claystone, and sandstone. The contrasting distribution of susceptibility along several profiles reveals sharp lithological changes, interpreted as indications of a local fault zone that influences the subsurface magnetic distribution.